A mixed method look at state growth management policy - Howell-Moroney, Michael E. (2008)
Using a mixed method approach, this article investigates growth management policy in the American states, presenting an event history analysis of state growth management policy adoptions, supplemented by a case study of growth management's evolution in the state of Maryland. Empirical results from the event history analysis suggest that growth pressures, the countervailing forces of state environmentalism and building interests, stronger gubernatorial powers, and citizen liberalism are all important factors associated with state adoptions of growth management. The Maryland case triangulates and contextualizes these key empirical findings, demonstrating the importance of those variables in a state-specific context. Beyond triangulating the empirical results, Maryland's legislative history with growth management highlights the importance of civic engagement as a means to both formulate and build sustained support for state growth management policy, even in the face of significant opposition from development interests. - Reproduced.
Keywords: Management